Topotactic hydrogen in nickelate superconductors and akin infinite-layer oxides ABO2 - Si, Liang; Xiao, Wen; Kaufmann, Josef; Tomczak, Jan M.; Lu, Yi; Zhong, Zhicheng; Held, Karsten (Physical review letters, 2020)
Superconducting nickelates appear to be difficult to synthesize. Since the chemical reduction of ABO3 [rare earth (A), transition metal (B)] with CaH2 may result in both ABO2 and ABO2H, we calculate the topotactic H binding energy by density functional theory (DFT). We find intercalating H to be energetically favorable for LaNiO2 but not for Sr-doped NdNiO2. This has dramatic consequences for the electronic structure as determined by DFT+dynamical mean field theory: that of 3d9 LaNiO2 is similar to (doped) cuprates, 3d8 LaNiO2H is a two-orbital Mott insulator. Topotactic H might hence explain why some nickelates are superconducting and others are not.
Gesehen am 13.05.2020
Im Titel ist die Zahl "2" in ABO2 tiefgestellt